The use of artificial intelligence in the public sector in Shanghai: ambition, capacity and reality - Todaro, Diego (Springer Nature Singapore, 2024)
Chapter 1: Approaching China’s “Artificial intelligence development highland” -- Chapter 2: Artificial intelligence in the public sector in Shanghai: conceptualization, context, and capacity -- Chapter 3: The AI policy environment of Shanghai -- Chapter 4: The AI ecosystem of Shanghai -- Chapter 5: Public sector AI applications in Shanghai -- Chapter 6: Ambition, capacity, reality, insights and prospects.